Lipoatrophy and metabolic disturbance in mice with adipose-specific deletion of kindlin-2 - Gao, Huanqing (JCI Insight, 2019)
Kindlin-2 regulates integrin-mediated cell adhesion to and migration on the extracellular matrix. Our recent studies demonstrate important roles of kindlin-2 in regulation of mesenchymal stem cell differentiation and skeletal development. In this study, we generated adipose tissue–specific conditional knockout of kindlin-2 in mice by using Adipoq-Cre BAC–transgenic mice. The results showed that deleting kindlin-2 expression in adipocytes in mice caused a severe lipodystrophy with drastically reduced adipose tissue mass. Kindlin-2 ablation elevated the blood levels of nonesterified fatty acids and triglycerides, resulting in massive fatty livers in the mutant mice fed with high-fat diet (HFD). Furthermore, HFD-fed mutant mice displayed type II diabetes–like phenotypes, including elevated levels of fasting blood glucose, glucose intolerance, and peripheral insulin resistance. Kindlin-2 loss dramatically reduced the expression levels of multiple key factors, including PPARγ, mTOR, AKT, and β-catenin proteins, and suppressed adipocyte gene expression and differentiation. Finally, kindlin-2 loss drastically reduced leptin production and caused a high bone mass phenotype. Collectively, these studies establish a critical role of kindlin-2 in control of adipogenesis and lipid metabolism as well as bone homeostasis.